Sepsis in Infants: Analysis of Bacterial Pathogens and their Antibiotic Susceptibility, A Study at Government Tertiary Care Hospital, Karachi - Masood Hassan Rao; Sadia Khan; Tooba Waseem; Sabah Naeem; Sadaf Sabir (Journal of the Dow University of Health Sciences, 2013)
Objective: